COMMERCIALIZATION METHODS OF PROJECTS IN THE FIELD OF NANOTECHNOLOGY - Myrzakhmet, M. K.; Akhmet, S. T.; Myrzakhmet, Z. K. (Recent Contributions to Physics, 2009)
The basic tool of the state should be cofinancing of projects with the private capital at the most risk stages. The basic moment for innovative activity is delivery of loans for the long period, till 10 years. Release of highly skilled managers by means of creation at national universities of innovation business schools will give the chance to pass to system of training of active managers which will bring the newest concepts and management tools on the enterprises. It is necessary to explain and spread management methods innovations, developing among students of universities competitive actions, in particular, business game «Innovation management».